Effect of some Agricultural treatments in mitigation of aerial infestation of woolly apple aphid Eriosoma lanigerum (Hausmann) and on some chemical characteristics of apple fruit - ديوب, سمر; رشيد خربوتلي,; نبيل أبو كف, (Latakia University Journal -Biological Sciences Series, 2024)
The experiment was carried out during seasons of 2020 and 2021 in orchard of clonal rootstocks in Kassab village on two apple cultivars "Royal gala", "Granny smith" fifteen years old and grafted on M. sylvestris and also applied on the rootstock Malus sylvestris L. (Mill). nine years. the infestation of woolly apple aphid is made by putting shoots full of woolly apple aphid for each tree in four directions on the terminal shoots for (18) trees. Then estimated the percentage of aerial infestation after four months, and also The total soluble solids total sugars, total acidity in eight treatments were control, the intermediate pruning, the fertilizer + the foliar sprays once, utilization the parasitoid Aphelinus mali (Haldman) , intermediate pruning+ fertilizer + foliar sprays once, intermediate pruning + utilization the parasitoid A. mali , fertilizer + foliar sprays once + utilization the parasitoid A. mali, intermediate pruning + fertilizer + foliar sprays once + utilization the parasitoid A. mali.mThe results showed that the interaction for studied treatments the pruning+ fertilizer + foliar sprays utilization parasitoid A. mali reduced the aerial infestation of (WAA) significantly in parasitism treatment in the cultivar Granny smith and the rootstock Malus sylvestris (Mill). Whereas the lower percentage of aerial infestation were the cv" Royal gala in the treatment (fertilizer + foliar sprays once + utilization the parasitoid A. mali) reached (4.97) % in compared with control (14.36) % . As well as the interaction for studied treatments improved the content of apple fruit of the total soluble solids, total sugars, and decreased the total acidity. The total soluble solids were the highest in the rootstock fruit M. sylvestris (Mill) (14.55) % compared to control (9.10% (. But the highest content of total sugars were (12.97) % compared to control (6.08) % for the cv "Granny smith", the lower percentage of total acidity were achieved (0.31) % compared to control (0.94) % in the treatment (intermediate pruning + fertilizer + foliar sprays once + parasitism) in the cultivar "Royal gala", and "Granny smith"(0.30) %compared to control %( 0.67) in the same treatment As a result of the statistical analysis. there were significant differences between all the studied treatments with the superiority of the treatment (intermediate pruning+ fertilizer + foliar sprays once+ utilization the parasitoid A. mali on tested treatments and control. So we recommend with this treatment because it improved remarkably the content of total soluble solids, total sugars and on the contrary decreased the total acidity.